Novel Ideas : Contemporary Authors Share the Creative Process - Denman, Margaret-Love; Shoup, Barbara (Book collections on Project MUSE., 2009)
From the Publisher: Novel Ideas provides a substantial introduction to the elements of fiction followed by in-depth interviews with successful novelists who speak with candor and insight into the complex process by which a novel is made. This edition includes new and updated interviews as well as writing exercises to enhance its use in the writing classroom. Dorothy Allison recalls "deliciously self-indulgent" days of writing in her bathrobe, wrapped in misery and exultation; Peter Cameron explains how he made the move from short fiction to the novel with the aid of a music composer's notebook to track the movement of his characters. Writers as different as Ha Jin, Jill McCorkle, Richard Ford, and Michael Chabon describe their unique approaches to their work while consistently affirming the necessity of committing to the hard effort of it while also remaining open to surprise. Aspiring novelists will find hands-on strategies for beginning, working through, and revising a novel; accomplished novelists will discover new ways to solve the problems they face in process; and serious readers of contemporary fiction will enjoy a glimpse into the way novels are made. Includes interviews with: Dorothy Allison; Larry Brown; Peter Cameron; Michael Chabon; Michael Cunningham; Robb Forman Dew; Richard Ford; Ha Jin; Patricia Henley; Charles Johnson; Wally Lamb; Valerie Martin; Jill McCorkle; Sena Jeter Naslund; Lewis Nordan; Sheri Reynolds; S.J. Rozan; Jane Smiley; Lee Smith; and Theodore Weesner